الإجتهاد والمبادىء التي يجب مراعاتها فيه - حمدان، إياد فوزي Hamdan, Eyad Fawzi (جامعة السودان للعلوم والتكنولوجيا - معهد العلوم والبحوث الإسلامية, 2010)
تعالج هذه الدراسة موضوعا مهما تمس الحاجة إليه في كل عصر فهي تبين أن الأحكام الشرعية تتغير بتغير الزمان أو المكان أو الأحوال أو العرف أو المصلحة أو سد الذرائع . وإن الأحكام القابلة للتغير هي الأحكـام الاجتهادية. كما تناولت الدراسة بعض الرسائل المتعلقة بالموضوع مثل تعريف الاجتهـاد لغـة واصـطلاحا والأدلة الدالة على مشروعية الاجتهاد والشروط الواجب توافرها في المجتهد. \ خلصت الدراسة إلى الآتي: \ \ •\ يجب في زماننا الآن العمل بالاجتهاد الجماعي لأنه أحوط وأبعد عن الخطأ. \ •\ الاجتهاد المعتبر هو الصادر عن أهله. \ •\ من المبادئ الواجب اعتبارها عند الاجتهاد مبدأ تغير الأزمنة والأمكنة، العرف، المصلحة، سـد الـذرائع الواجب مراعاتها. This study addresses a crucial subject that we desperately need in every time of life. It discusses that juristic laws change according to changes in the time, place, circumstances, customs and the bublic interest. These changeable laws are the discretionary ones. \ The study has also tackled matters concerned with the subject matter of the study such as the definition of Ijtihad (or jurisprudence) denotatively and connotatively and the necessary condition that characterize the jurist. Finally, the study has concluded that people must work collectively in order to avoid human error. Thus, the considerable Ijtihad is the one issued by the specialist and competent authorities. Another important principle that should be considered in the Ijtihad is that juristic principles change according to changes in time, place, customs, public interest and sad al-zarai3.
Keywords: الأحكام الشرعية -- الأحكام الإجتهادية -- الشريعة الإسلامية -- الحياة اليومية